Industrial training report: Bertam Properties Sdn. Bhd. / Muhammad Kamil Anuar - Anuar, Muhammad Kamil (Universiti Teknologi MARA, Perlis, 2023)
Industrial training is one of the compulsory courses for every student to qualify for the award of Bachelor. Students must pass the industrial training to get the Bachelor. This industrial training aims to provide early exposure to students about the nature of work for each field. I have been training industry in Bertam Properties Sdn Bhd for this session for 24 weeks starting on 29 August 2022 to 10 February 2023. Within these 24 weeks, I have the opportunity to learn a variety of knowledge inside Property Industry.I was placed in the Finance Department, Bertam Properties Sdn Bhd .This company divides into five segment led by the Group of Executive Officer, Finance Department, Sales and Marketing Department, Project Department and Admin/It Department. This Department consists of 9 personnelstaff that works closely with each other. I am under the supervision of Puan Jamilah Ibrahim her position is Assistant Finance Manager in Finance Department. From the beginning, I always put a mindset to grab every possible opportunity given to grow and build my own personal development towards my career path. The idea of having an Industrial Training is to prepare every student for the upcoming challenges, the sweet and bitter experience that will shape and build strength to face the reality of the real working life. This report begins with student’s profile which is my updated resume that will be used to apply for employment. The resume contains my education background, work experiences, my skills and extra-curricular activities that I joined. Then, it moves to the company’s profile that contains name, location, background, vision, mission, objective, organizational structure. Next, I will share about the training’s reflection that includes the duration of the internship, the work experiences and what I gain from doing internship at Bertam Properties Sdn bhd. Then, there will be SWOT analysis along with discussions and recommendations that I can possibly point out to make the discussion more interesting. In a nutshell, the conclusion that I can conclude from spending 24 weeks of my time to experience the eye-opening experience that prepares me for the real journey of life ahead.